Phytoconstituents, antioxidant and antiglycation activity of Chrysophyllum cainito L., Hancornia speciosa Gomes and Plinia glomerata Berg. fruits - GUSTAVO R. MARTINS; JOÃO LUIZ BRONZEL JUNIOR; FILIPE O. GRANERO; CÉLIA CRISTINA M. FIGUEIREDO; LUCIANA P. SILVA; REGILDO MÁRCIO G. DA SILVA (Anais da Academia Brasileira de Ciências, 2023)
Abstract The present study verified the presence of phytoconstituents and evaluated antioxidant (DPPH, FRAP, NO and TBARS tests) and antiglycation (REM test) activities of unconventional wild edible fruits Chrysophyllum cainito, Hancornia speciosa and Plinia glomerata. It was verified the presence of phenolic compounds for all fruits and flavonoids were observed only for C. cainito, which presented in its peel the highest total phenols (90.34 μg GAE mg-1) and flavonoids (30.4 μg RE mg-1) content. Sugar concentration was significant for all fruits, where H. speciosa showed the highest reducing sugar content (576.12 mg g-1) and C. cainito pulp showed the highest total sugar content (858.67 mg g-1). All fruits presented vitamin C and carotenoids, highlighting P. glomerata with the best results for ascorbic acid (2260.94 mg 100 g-1) and carotenoids (59.62 µg g-1). Extracts presented antioxidant activity, highlighting C. cainito peel that presented 65.64% (DPPH), 231.34 µM TE L-1 (FRAP), 49.34% (NO) and 22.56% (TBARS), while in antiglycation evaluation, P. glomerata showed evident activity. Therefore, it was possible to determine different phytoconstituents, and antioxidant and antiglycation activities of the fruits. These data provide subsidies for application of these fruits in new studies, to increase knowledge and preservation of these species.